Long-term excessive salt consumption alters villous and crypt morphology and the protein expression of uroguanylin, TRPV6 and PMCA1b in the rat small intestine - Natchayaporn Thonapan; Kannikar Wongdee; Sirion Aksornthong; Jarinthorn Teerapornpuntakit; Wacharaporn Tiyasatkulkovit; Nattapon Panupinthu; Narattaphol Charoenphandhu (PLoS ONE, 2025)
Although long-term high dietary sodium consumption often aggravates hypertension and bone loss, sodium in the intestinal lumen has been known to promote absorption of nutrients and other ions, e.g., glucose and calcium. However, whether high-salt diet (HSD) altered mucosal morphology, villous cell turnover and calcium transporter expression remained elusive. Herein, rats were treated with HSD containing 8% wt/wt NaCl for up to 5 months. HSD rats exhibited a marked increase in sodium intake with high fecal and urinary sodium excretion, as compared to the control group treated with normal diet. Intestinal histomorphometry revealed increasing of crypt depth and villous height in 3- and 4-month HSD groups, respectively, consistent with larger mucosal-to-serosal amplification ratio that reflected an increased surface area for nutrient absorption. The signals of Ki-67-positive cells was enhanced in the crypts as visualized by multiphoton fluorescence microscopy, whereas the TUNEL-positive cells were decreased in the villi of HSD, suggesting greater crypt cell proliferation and a reduction of villous cell apoptosis. Confocal microscopy showed higher expression of TRPV6 protein in the villous tip of HSD, while PMCA1 expression was increased in villous tip and crypt areas. The percentage of cells with highly expressed uroguanylin—an endogenous intestinal natriuretic peptide—was significantly higher in HSD group. In conclusion, HSD profoundly changed the intestinal morphology and turnover of epithelial cell, increased the expression of calcium transporters and uroguanylin. Our findings reflect pathophysiological adaptations in the intestine, which might be another target organ for drug discovery against HSD-induced osteopathy in the future.